Virtual friday prayer practices during the Covid-19 pandemic in Indonesia - Qudsy, Saifuddin Zuhri; Ghozali, Mahbub; Faiz, Abd. Aziz
This study aims to analyze the practice of virtual Friday prayers implemented to provide convenience of worship during the pandemic in Indonesia. Ease of access and fulfillment of social distancing that is relevant to the conditions of the Covid-19 outbreak is considered a solution to solving religious problems in the context of a pandemic. To achieve this goal, this research uses qualitative methods with data collection techniques through observation and documentation which are analyzed using content analysis techniques. Research into the practice of virtual Friday prayers raises two main trends. The first trend is related to the need to shift the practice of conventional Friday prayers to virtual Friday prayers which are considered relevant in dealing with the pandemic. The second trend is related to the impact of changes in practice that produce new terms in the implementation of virtual Friday prayers. The shift in worship practices with various terms that are considered to provide solutions for ease of worship does not go hand in hand with efforts to reconceptualize the main provisions that make Friday prayers valid in Islamic law (fiqh). The concept of the continuity of the movements of the imam and the congregation, which is a requirement for the validity of prayer with the condition of being in one place, is not owned by virtual Friday prayers, so its validity is doubtful. Re-conception is needed to maintain the continuation of the virtual Friday prayer, which is considered easy and relevant to the pandemic context. Ignoring the availability of supporting arguments has an impact on identifying the practice of virtual Friday prayers as an effort to appropriate religion with technology that is prone to conflict and debate in society.